2019
DOI: 10.7554/elife.42305
|View full text |Cite
|
Sign up to set email alerts
|

Insights into AMS/PCAT transporters from biochemical and structural characterization of a double Glycine motif protease

Abstract: The secretion of peptides and proteins is essential for survival and ecological adaptation of bacteria. Dual-functional ATP-binding cassette transporters export antimicrobial or quorum signaling peptides in Gram-positive bacteria. Their substrates contain a leader sequence that is excised by an N-terminal peptidase C39 domain at a double Gly motif. We characterized the protease domain (LahT150) of a transporter from a lanthipeptide biosynthetic operon in Lachnospiraceae and demonstrate that this protease can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 67 publications
4
123
0
Order By: Relevance
“…Examining these sequence motifs also reveals that in addition to the long-recognized FxLD sequence motif in the leader peptides of class I LanAs [36], a number of class I LanAs from Bacteroidetes have a LxLxKx 5 L motif instead. Many of the leader peptides that contain this motif end with a Gly-Gly sequence, and a C39-family Cys protease that removes leader peptides at GG sites [37,38] is often encoded in the corresponding clusters. This GG leader motif has previously only been observed in class II [39] and III LanAs [40].…”
Section: Resultsmentioning
confidence: 99%
“…Examining these sequence motifs also reveals that in addition to the long-recognized FxLD sequence motif in the leader peptides of class I LanAs [36], a number of class I LanAs from Bacteroidetes have a LxLxKx 5 L motif instead. Many of the leader peptides that contain this motif end with a Gly-Gly sequence, and a C39-family Cys protease that removes leader peptides at GG sites [37,38] is often encoded in the corresponding clusters. This GG leader motif has previously only been observed in class II [39] and III LanAs [40].…”
Section: Resultsmentioning
confidence: 99%
“…Studies of heterotrophic bacteria established a model in which the GG‐motif leader peptide is cleaved off during transport by the N‐terminal domain of a transporter component, which belongs to the Peptidase C39 protein family (Michiels et al, ; Bobeica et al, ). Mutation of the conserved cysteine of the peptidase domain of the protein encoded by Synpcc7942_1133 of S. elongatus (denoted PteB for Peptidase transporter enabling Biofilm), which belongs to the C39 family, indicated its requirement for biofilm development and for proper secretion of the EbfG small proteins (Parnasa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The leader peptides of all nine LahA peptides are conserved and, like the prochlorosins, are members of the Nif11‐like protein family ending with a double Gly motif (Figure C). Our previous study demonstrated that the LahT150 protease domain recognized this motif for all nine substrates . In contrast, the sequences of the corresponding core peptides exhibit a high degree of sequence divergence and five of the nine peptides distinctly lack Cys residues (Figure B).…”
Section: Resultsmentioning
confidence: 86%
“…Recently, we reported a highly substrate tolerant protease domain of the bifunctional transporter LahT encoded in a putative lanthipeptide biosynthetic gene cluster ( lah ) in Lachnospiraceae bacterium C6A11. This domain called LahT150 efficiently removes leader peptides from a large number of double glycine motif‐containing peptides . LahT is a member of the family of ABC‐transporter maturation and secretion (AMS) proteins (also called peptidase‐containing ATP‐binding transporters, PCAT) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation